Seeking support through solidarity: female leader’s experiences of workplace solidarity in male-dominated professions - Pillay-Naidoo, Daphne; Vermeulen, Corlette (Frontiers in Psychology, 2023)
Introduction While there is a plethora of research that documents the numerous barriers affecting female leaders in the modern workplace, there is a lack of literature which focuses on strategies or motivating resources that women use to navigate the workplace environment. Despite facing significant barriers in their leadership journeys, there are female leaders who are able to overcome these barriers to achieve leadership positions. These women leaders draw on personal and external motivating factors to assist them in dealing with the challenges associated with being a female leader as a result, research on motivating strategies for women’s career progression is a research topic that warrants immediate attention. Female solidarity as a motivating resource has been gaining traction in the field of leadership studies and can be seen as a supportive resource that can be used by current and aspiring female leaders to progress in underrepresented environments. Although female solidarity is but only one of the many strategies that can be implemented to motivate women in leadership positions, the increase of female solidarity in the workplace is expected to alleviate the conditions that reinforce essentialist notions of the “queen bee syndrome” in which women are seen as unsupportive of each other. Method A qualitative research approach was used for this study, following an interpretive descriptive design. A total of 13 semi-structured interviews were conducted with female leaders in male-dominated professions within South Africa. Data was analysed using thematic content analysis. Results Results of the study were analyzed in line with three primary content areas, i.e., barriers to female solidarity in the workplace, benefits of female solidarity in the workplace and workplace interventions to increase solidarity. Discussion In the context of the study the predominant barriers to female solidarity within male-dominated workplaces were identified as unfair workplace behaviours, generational beliefs, societal expectations, organisational cultures, stereotypes and stigmas. The benefits of female solidarity within male-dominated workplaces were identified as career shaping mentorship, female recognition, female representation and female support. Lastly, the interventions that can be implemented to increase female solidarity within male-dominated workplaces were conceptualised as networking, transforming the company culture, socialisation and mentorship.